BUILDING HIGH-QUALITY LOCAL GOVERNMENT FINANCIAL STATEMENTS: UNRAVELING THE IMPACT OF GOVERNMENT INTERNAL CONTROL SYSTEM AND ORGANIZATIONAL COMMITMENT - Muliasri, Hawarini; Putri, Intan Lifinda Ayuning (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The low quality of Local Government Financial Statement (LKPD) may lead to false decision-making that declines public trust. This research examines the effect of the Government Internal Control System (SPIP) on the LKPD quality involving organizational commitment as a moderating variable. The study was conducted in Bulungan Regency, with a sample consisting of financial department employees. This study applies a quantitative approach and utilizes SPSS software for hypothesis testing. The study's results prove that SPIP positively influences the quality of LKPD, while organizational commitment does not moderate the correlation between SPIP and LKPD. Although various studies have examined similar topics, the findings remain inconsistent. The absence of similar research in Bulungan Regency positions this study to provide a new perspective and serve as a valuable reference for other regions with comparable characteristics. In addition, this study aims to enrich the relevance of agency theory in the public sector and serve as a basis for optimizing LKPD quality by reinforcing the effective implementation of each SPIP component.